The Use of Natural Language Processing Model in Literary Style Analysis of Chinese Text - Ye Jinze (ITM Web of Conferences)
In recent years, research on Natural Language Processing (NLP) has made consistent progress and has become a popular topic. As a promising branch of Machine Learning, NLP focuses on the understanding, generating and analysing of human languages. The applications of NLP include chatbots and language translation. This paper represents a HanLP based NLP model. The model is capable of analysing the literary style of given Chinese text by quantifying the literary style of the text on the basis of five fundamental elements, namely literary grace, sentiments, momentum, climate and lingering charm. This paper presents the input and output data of the research and conducts analyses on these data. Moreover, this paper draws a conclusion on the deviation rate and robustness of the model. It is reckoned that this model initially possesses the function of literary style analysis of Chinese text. The research, per se, along with its data, is capable of being reference for research in NLP and related fields.